DAYA DUKUNG DAN INDEKS KESESUAIAN WISATA DI PANTAI JERMAN DAN PANTAI SEGARA, KECAMATAN KUTA, KABUPATEN BADUNG, PROVINSI BALI - Sitinjak, Sonia Sarah; Restu, I Wayan; Pertami, Nyoman Dati (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2025)
Segara Beach and German Beach are one of the beaches located in Kuta District, Badung Regency, Bali. Segara Beach and German Beach have tourist destinations such as swimming, sunbathing, seeing the scenery, and sitting back, so that local and foreign tourists can enjoy the tourist attractions at Segara Beach and German Beach. Tourism development must be based on the principle of sustainable development (Sustainable Development Goals). Tourism development has a direct impact on the environment and can reduce the sustainability of existing natural resources, therefore it is necessary to know the carrying capacity of the tourism area (DDK) and the tourism suitability index (IKW) in order for further development to be very important based on the availability of data or information about carrying capacity and suitability index and evaluation of the potential conditions of tourist attractions at Segara Beach and German Beach, so it is very urgent to do. Data collection was carried out in March-April 2024 using quantitative and qualitative descriptive methods. The data analysis method uses carrying capacity analysis and tourism suitability index by calculating the type of beach, basic water material, beach width, water depth, water clarity, current speed, beach slope, land cover, dangerous biota, and fresh water availability. Based on the results of the tourism suitability index analysis, the results obtained at stations 1, 2, and 3 were 2.9, which is included in the very suitable category with a carrying capacity for the swimming category of 980 people/day, the viewing category of 6,971 people/day, the sitting and relaxing category of 5,346 people/day, and the sunbathing category of 4,386 people/day.